Bicyclic γ-amino acids as inhibitors of γ-aminobutyrate aminotransferase. (3rd March 2016) - Pinto, Andrea; Tamborini, Lucia; Pennacchietti, Eugenia; Coluccia, Antonio; Silvestri, Romano; Cullia, Gregorio; De Micheli, Carlo; Conti, Paola; De Biase, Daniela
Abstract: The γ-aminobutyrate (GABA)-degradative enzyme GABA aminotransferase (GABA-AT) is regarded as an attractive target to control GABA levels in the central nervous system: this has important implications in the treatment of several neurological disorders and drug dependencies. We have investigated the ability of newly synthesized compounds to act as GABA-AT inhibitors. These compounds have a unique bicyclic structure: the carbocyclic ring bears the GABA skeleton, while the fused 3-Br-isoxazoline ring contains an electrophilic warhead susceptible of nucleophilic attack by an active site residue of the target enzyme. Out of the four compounds tested, only the one named (+)-3 was found to significantly inhibit mammalian GABA-AT in vitro . Docking studies, performed on the available structures of GABA-AT, support the experimental findings: out of the four tested compounds, only (+)-3 suitably orients the electrophilic 3-Br-isoxazoline warhead towards the active site nucleophilic residue Lys329, thereby explaining the irreversible inhibition of GABA-AT observed experimentally.